Analisis dan Desain Sistem Informasi Pembayaran Sumbangan Pembinaan Pendidikan (SPP) di SMK Avicena Rajeg - Taufiq, Rohmat; Magfiroh, Diyah Ayuni; Yusuf, Dadang; Yulianti, Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2020)
As the present era progresses, information technology (IT) is expanding enormously. In the world of education, mainly primary and secondary school, some jobs carried out manually. SMK Avicena Rajeg is a place where the writer carried out practical work, still inputting data using Microsoft excel — analyzing the SPP payment information system in SMK Avicena Rajeg which is means for supporting TU staff performance. The method used by the writer includes interview method, observation method, literature method and Unified Modelling Language (UML) to describe a running model system and proposed system. With the production of an SPP payment information system analysis in the discussion that the writer described could be used as consideration in the process of developing student payment information systems. The writer suggested that the student tuition payment process should be computerized, as of the data that managed can be well-integrated, for example, by using the PHP programming language and MySQL database server.